2006
DOI: 10.1051/0004-6361:20053952
|View full text |Cite
|
Sign up to set email alerts
|

Triggered massive-star formation on the borders of Galactic H II regions

Abstract: Abstract. Young massive stars or clusters are often observed at the peripheries of H  regions. What triggers star formation at such locations? Among the scenarios that have been proposed, the "collect and collapse" process is particularly attractive because it permits the formation of massive objects via the fragmentation of the dense shocked layer of neutral gas surrounding the expanding ionized zone. However, until our recent article on Sh 104, it had not been convincingly demonstrated that this process ac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
171
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 160 publications
(186 citation statements)
references
References 64 publications
(45 reference statements)
11
171
2
2
Order By: Relevance
“…(This mechanism is often called "radiation-driven implosion" of a condensation, but "radiationdriven compression" would be better as no observations indicate that star formation occurs during the implosion.) Good illustrations of star formation triggered by the expansion of H ii regions are given by the RCW 79 (Zavagno et al 2006) and RCW 120 ) bubbles.…”
Section: The Neutral Environment Of the Bubbles As Seen By Atlasgalmentioning
confidence: 99%
“…(This mechanism is often called "radiation-driven implosion" of a condensation, but "radiationdriven compression" would be better as no observations indicate that star formation occurs during the implosion.) Good illustrations of star formation triggered by the expansion of H ii regions are given by the RCW 79 (Zavagno et al 2006) and RCW 120 ) bubbles.…”
Section: The Neutral Environment Of the Bubbles As Seen By Atlasgalmentioning
confidence: 99%
“…Several H ii regions have been studied individually in the context of triggered Herschel is an ESA space observatory with science instruments provided by European-led Principal Investigator consortia and with important participation from NASA. star formation, focusing on the associated neutral material and the young stellar population (Zavagno et al 2006;Deharveng et al 2009;Pomarès et al 2009;Bieging et al 2009). These studies have shown that the expansion of H ii regions can trigger the formation of new stars of all masses.…”
Section: Introductionmentioning
confidence: 99%
“…3.4), we use the analytical model of Whitworth et al (1994) for the case of an expanding Hii region which predicts the time at which the fragmentation occurs. We have followed the analysis of Zavagno et al (2006), deriving the time when the fragmentation may have occurred (t frag ), and the size of the Hii region at t frag (R frag ), given by t frag = 1.56 a 0. …”
Section: Triggered Star Formation Scenariomentioning
confidence: 99%
“…The derived value of n 0 is higher than the density limits required for the fragmentation according to the Whitworth et al scenario, which indicates that the C&C process might be important in the collected layers of molecular gas. As pointed out by Zavagno et al (2006), the estimates presented above are rough, since the Whitworth et al model assumes expansion into a homogeneous medium and many uncertainties remain concerning to the uniformity of the medium where Gum 31 evolved (see Sect. 3.1).…”
Section: Triggered Star Formation Scenariomentioning
confidence: 99%